ANALYSIS MEASUREMENT OF RELATIVE PERMITTIVITY ON THE TEXTILE MATERIALS USING CAVITY REFLECTION TRANSMISSION PERTURBATION - Wenda Adi Irawan; Levy Olivia Nur; Bambang Setia Nugroho; Achmad Munir (IST AKPRIND Yogyakarta, 2018)
The information characteristic of dielectric material is one of important properties in design of wearable absorber. The studies were also performed to investigate the EM properties of textile materials when being exposure by EM waves especially for wearable absorber application. This is because the effects of EM waves emitted from electronic equipment on human health being a current problem to solve. In this paper, the analysis measurement of relative permittivity of textile materials is focused based on cavity reflection transmission perturbation method. The cavity perturbation method has difficulties to measure the objects like cuts the textile into a smaller piece than measurement device but has good accuracy. While transmission reflection method is easy to measure however has less accurate. The method that uses combination from reflection transmission method, cavity perturbation method and a rectangular waveguide which has high accuracy. According to textile relative permittivity measurement, the proposed method is numerical analyzed and then experimental inspected for some known dielectric materials. From the result of measurement relative permittivity for some textile materials has specific characteristic depend on each textiles and can be used as reference to design absorber. It show the proposed method is compatible for measure the textile characteristics in design antennas, reflectors, especially for wearable absorber.